The effect of TQM practices on technological innovation capabilities: Applying on Malaysian manufacturing sector - Yusr, Maha Mohammed; Mohd Mokhtar, Sany Sanuri; Othman, Abdul Rahim (Center for Quality, University of Montenegro and Center for Quality, University of Kragujevac, Serbia, 2014)
The relationship between TQM practices and innovation performance had drawn the attention of several scholars during last decade, however, this relationship still not clear and inconclusive. Therefore, this study is one of the attempts that aim to clarify the nature of this relationship.Reviewing the past studies reveals that there is somewhat ignoring in examining the indirect relationship between TQM and innovation performance.Thus, to determine and explore the effect of applying TQM practices within the organization on innovation performance, this study is aiming to investigate the relationship between TQM practices and technological innovation capabilities in Malaysian context.The obtained result of SmartPLS statistical analysis confirmed the positive effect of applying TQM practice on technological innovation capabilities. Moreover, the findings also provide an indication regarding the level of occurrence of technological innovation capabilities among Malaysian manufacturing companies. According to the output several recommendations have been highlighted to the managers of the companies.